Motion Analysis of Payuang Sarampak Dance in Lindang Urek Studio, Payakumbuh Timur Subdistrict, Payakumbuh City - Nurul Fazila Ismail; Herlinda Mansyur (Universitas Negeri Padang, 2024)
This study aims to describe and analyze the Payuang Sarampak Dance Movement in Sanggar Lindang Urek, East Payakumbuh District, Payakumbuh City. This type of research is qualitative using descriptive methods. Data were obtained by literature study, observation, interviews and documentation. The object of research is Payuang Sarampak Dance at Sanggar Lindang Urek. The main instrument is the researcher himself and requires tools in collecting data in the field, namely stationery and cellphone cameras. Data analysis techniques are by means of data collection, data reduction, data presentation and data examination. The results showed that Payuang Sarampak Dance in Sanggar Lindang Urek, East Payakumbuh District, Payakumbuh City was arranged by Bambang Irawan and the results found were aspects of space, time and energy of Payuang Sarampak dance. The process of creating Payuang Sarampak dance began with Mr. Bambang Irawan inspired by everyday life, namely the association of Minangkabau youth and women who still uphold customs and religion. This dance has 23 varieties of movements. The costumes used by female dancers are baju kurung, songket, tokah, suntiang, necklace, koteh-koteh, lame, laca and flowers for headdress. While male dancers wear purple loose clothes, black pants, scarves, sides, belts and use headdresses. The musical instruments used are gandang, bass guitar, violin, hi-hat, talempong, bansi, sarunai, accordion and tasa.